Labels and epilepsy — An online survey of patients and those close to them - Friedrich, Latica; Sruk, Ana; Bielen, Ivan (Epilepsy & behavior, 2019)
Publications on the topic of appropriate labels for someone with diagnosed epilepsy have so far almost exclusively consisted of views of professionals in this field. We conducted an online study of patients treated for epilepsy and persons close to them with the aim of identifying which label they prefer, whether they oppose the term “epileptic”, and which characteristics are related with their preferences. In total, 328 responses were analyzed. Subjects mostly favored “person-first” terminology (“person having epilepsy” and “person with epilepsy”), and 53.9% disapproved of the term “epileptic”. Parents of patients are more likely than patients themselves to favor the label “person having epilepsy” and to disapprove of the label “epileptic”. These results can help with shaping future terminology recommendations. •Views on labels in epilepsy were researched among patients and caregivers.•Person-first terminology was favored, and 53.9% opposed the term “epileptic”.•Parents more often disapprove of the label “epileptic” than patients themselves.